(E)-1-(4-Decyloxyphenyl)-3-(4-hydroxy-phenyl)prop-2-en-1-one - Ibrahim, Abdul Razak; Fun, Hoong-Kun; Zainab, Ngaini; Siti Muhaini, Haris Fadzillah; Hasnain, Hussain (2009)
In the title compound, C25H32O3, the asymmetric unit containstwo crystallographically independent molecules: both enonegroups adopt ans-cisconfiguration. In the crystal, O—HOand C—HO intermolecular interactions form bifurcatedhydrogen bonds, which generateR12(6) ring motifs. Theseintermolecular interactions link the molecules into one-dimensional chains along the [101] direction. The crystalstructure is further stabilized by C—Hinteractions.